2003
DOI: 10.1348/000712603762842129
|View full text |Cite
|
Sign up to set email alerts
|

‘There's no smoke without fire’: Are male ex‐partners perceived as more ‘entitled’ to stalk than acquaintance or stranger stalkers?

Abstract: In a stalking scenario, the prior relationship between and the gender of stalker and victim were systematically manipulated in order to judge culpability and consequences for the persons involved. Written vignettes were presented to 168 participants who responded via seven Likert scales. Stalker-victim relationship had three levels: ex-partner, acquaintance and stranger. In accordance with the 'Just World' hypothesis (Lerner, 1980), the victim was judged as having greater responsibility for the stalking when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
112
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 20 publications
28
112
2
1
Order By: Relevance
“…More recently, Sheridan, Gillett, Davies, Blaauw, and Patel (2003) examined the influence of the perpetrator-target relationship and perpetrator-target sex on perceptions of stalking among a sample of 168 UK students. Participants were presented with a oneparagraph vignette describing a 'typical' case of stalking that had been ongoing for a year.…”
Section: Perceptions Of Stalkingmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Sheridan, Gillett, Davies, Blaauw, and Patel (2003) examined the influence of the perpetrator-target relationship and perpetrator-target sex on perceptions of stalking among a sample of 168 UK students. Participants were presented with a oneparagraph vignette describing a 'typical' case of stalking that had been ongoing for a year.…”
Section: Perceptions Of Stalkingmentioning
confidence: 99%
“…According to Sheridan, Gillett et al (2003), the just world hypothesis (JWH) proposed by Lerner and Simmons (1966) offers an explanation for the finding that the perpetratortarget relationship influences perceptions of stalking. The JWH asserts that people need to believe in a 'just world' in which people get what they deserve, or conversely, 'deserve what they get' (Lerner & Simmons, 1966).…”
Section: Just World Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, the body of research indicates that behaviour is more likely to be considered stalking when the behaviour is persistent (Dennison, 2007;Dennison & Thomson, 2002;Phillips et al, 2004;Scott & Sheridan, 2011), when the perpetrator clearly intends to cause the target fear or harm (Dennison, 2007;Dennison & Thomson, 2002;Phillips et al, 2004;Scott & Sheridan, 2011), and when the perpetrator is portrayed as a stranger rather than an 5 acquaintance or ex-partner (Cass, 2011;Phillips et al 2004;Scott, Lloyd, & Gavin, 2010;Scott & Sheridan, 2011;Sheridan, Gillett, Davies, Blaauw, & Patel, 2003). Research has also demonstrated that behaviour is more likely to be perceived to necessitate police intervention, and cause the target alarm, personal distress and to fear the use of violence when the behaviour is persistent and the perpetrator is portrayed as a stranger (e.g., Dennison, 2007;Hills & Taplin, 1998;Scott et al, 2010;Scott & Sheridan, 2011;.…”
Section: Introductionmentioning
confidence: 99%